Nanometer MOFs material, preparation method and application thereof
Patent Information
- Application Number
- CN202611467534.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
然而,该吸附剂的合成耗时长,难以满足快速制备与大规模生产的需求,且对氙气的捕获效果仍然有待进一步提高
[0016]本发明以同时含有氮和氧两类配位位点的氰尿酸为配体,基于软硬酸碱(HSAB)理论,氮原子优先与软酸Cu2+配位、氧原子优先与硬酸Sr2+配位,协同构筑出具有规则正八面体笼的周期性穿插框架结构,该Cu/Sr双金属协同配位策略赋予了MOFs材料高度有序的孔道结构与丰富的吸附活性位点,能够实现Xe/Kr的选择性吸附。本发明在微波辅助(10~850W,60~150℃,0.5~120 min)下合成,能够在分子级别实现能量的快速、均匀注入,使有机溶剂和配体氰尿酸瞬间偶极转动产生内热,从而在极短时间内形成晶核并促进晶体生长,有效避免了传统溶剂热法中反应时间长、粒径分布不均等问题。本发明在电子束辐照下合成(电子束电流1~10 mA,辐照总剂量80~8000 kGy)激发有机溶剂与反应物产生自由基、促进配位自组装的快速成核与晶化。本发明通过微波辅助合成以及电子束辐照合成可以快速获得高结晶度、高纯度的纳米MOFs材料,突破了传统溶剂热法粒径不可控、耗时长、工艺复杂、难以规模化的瓶颈。
Smart Images

Figure CN122978465A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of adsorption materials technology, specifically to a nano-MOF material, its preparation method, and its application. Background Technology
[0002] High-purity xenon (Xe) and krypton (Kr) have extremely high application value in high-tech fields such as optoelectronics, medicine, and aerospace. Therefore, the selective capture and separation of Xe and Kr is of great significance. The main methods for separating Xe and Kr include cryogenic distillation and adsorption. Among these, adsorption separation based on porous materials is considered a more promising technical approach due to its low energy consumption and ease of operation. Metal-organic frameworks (MOFs) possess characteristics such as high specific surface area, tunable pore size, easily modifiable structure, and diverse functions, demonstrating significant advantages in the field of gas adsorption.
[0003] Currently, most of the reported high-performance MOF materials are synthesized using traditional solvothermal methods, which typically require several days of reaction at high temperatures. This not only results in high energy consumption and long cycles, but also in the violent reaction that easily leads to excessive crystal growth and uneven particle size distribution, making it difficult to achieve efficient, rapid, controllable, and large-scale preparation of nanoscale MOF materials. For example, related technologies disclose a method for preparing metal-organic framework materials for adsorbing and separating xenon and krypton, including the following steps: (1) mixing hard acid metal salt, soft acid metal salt, organic ligand, alkali, and organic solvent in proportion, ultrasonically treating, and then putting them into a reaction vessel for solvothermal reaction; the organic ligand is an imide cyclic ketone organic ligand; (2) after the reaction, washing the product with methanol, and then vacuum drying to obtain the material; the alkali is sodium hydroxide, potassium hydroxide, aluminum hydroxide, or sodium carbonate; the organic solvent is methanol, ethanol, N,N-dimethylformamide, or N,N-dimethylacetamide; the hard acid metal salt is Sr 2+ Mn 2+ Fe 3+ At least one of chloride, nitrate, acetate, or carbonate salts; the soft acid metal salt is Ni. 2+ Cu 2+ Zn 2+ Cd 2+The adsorbent contains at least one of chloride, nitrate, acetate, or carbonate salts; the solvothermal reaction conditions are: reaction temperature 50~200℃, reaction time 24~72h. The metal-organic framework material CuSr(HC3O3N3)2 prepared by this technology was activated under vacuum at 120℃ for 24h. When this adsorbent was packed into an adsorption column, it achieved a xenon capture capacity of 92.6 mmol / kg in a xenon-krypton mixture (400 ppm Xe, 40 ppm Kr) at a flow rate of 5 mL / min. The adsorption performance remained stable after five consecutive adsorption-regeneration cycles. However, the synthesis of this adsorbent is time-consuming, making it difficult to meet the needs of rapid preparation and large-scale production, and the xenon capture effect still needs further improvement.
[0004] In recent years, although some studies have attempted to shorten reaction time using methods such as microwave-assisted synthesis, achieving rapid and uniform nucleation of precursors and precise control of grain size remains a technical challenge in the large-scale synthesis of nanoscale MOF materials. Therefore, there is an urgent need to develop a method for preparing nanoscale MOF materials with a short synthesis cycle, mild conditions, controllable nanoscale, and efficient adsorption and separation of Xe / Kr. Summary of the Invention
[0005] Therefore, the purpose of this invention is to provide a nano-MOF material, its preparation method, and its applications. The preparation method provided by this invention enables efficient, rapid, and controllable preparation of nano-MOF materials, and the prepared nano-MOF materials can efficiently adsorb and separate xenon (Xe) / krypton (Kr).
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing nano-MOF materials, comprising the following steps: By mixing cyanuric acid, copper source, strontium source, alkali metal hydroxide and organic solvent, and carrying out microwave-assisted reaction or electron beam irradiation reaction, nano-MOF materials are obtained. The conditions for the microwave-assisted reaction include: power of 10~850 W, temperature of 60~150℃, and time of 0.5~120 min; The conditions for the electron beam irradiation reaction include: an electron beam current of 1~10 mA and a total irradiation dose of 80~8000 kGy; The particle size of the nano-MOFs material is 15~300 nm.
[0007] Preferably, the molar ratio of cyanuric acid to copper source is 1:(0.25~1). The molar ratio of cyanuric acid to strontium source is 1:(0.25~1); The molar ratio of cyanuric acid to alkali metal hydroxide is 1:(1~2.5).
[0008] Preferably, the organic solvent includes methanol and / or ethanol.
[0009] The present invention also provides nano-MOF materials prepared by the preparation method described in the above technical solution.
[0010] This invention also provides the application of the nano-MOFs material described in the above technical solution in the adsorption and separation of xenon and krypton.
[0011] The present invention also provides a method for separating xenon and krypton, comprising the following steps: The nano-MOFs material described in the above technical solution is vacuum activated to obtain activated MOFs material; The activated MOFs material is used to adsorb a mixture of xenon and krypton, thereby achieving the separation of xenon and krypton.
[0012] Preferably, the vacuum activation temperature is 20~140℃ and the time is 4~36 h.
[0013] Preferably, the xenon content in the mixture is 200-600 ppm, and the krypton content is 20-60 ppm.
[0014] Preferably, the adsorption conditions include: an adsorption temperature of 0~40℃, a total system pressure of 100~300 kPa, and a mixed gas flow rate of 2~50 mL / min.
[0015] The present invention also provides a method for regenerating nano-MOFs materials after the separation method described above, comprising the following steps: desorbing the used nano-MOFs materials with helium to obtain regenerated nano-MOFs materials.
[0016] This invention uses cyanuric acid, which contains both nitrogen and oxygen coordination sites, as a ligand. Based on the hard-soft acid-base (HSAB) theory, the nitrogen atom preferentially binds to the soft acid Cu. 2+ Coordination, oxygen atom preference and hard acid Sr 2+Coordination and synergistic construction of a periodic interlaced framework structure with regular octahedral cages: This Cu / Sr bimetallic synergistic coordination strategy endows MOFs with a highly ordered pore structure and abundant adsorption active sites, enabling selective adsorption of Xe / Kr. This invention is synthesized under microwave assistance (10~850W, 60~150℃, 0.5~120 min), achieving rapid and uniform energy injection at the molecular level. This causes instantaneous dipole rotation of the organic solvent and cyanuric acid ligand, generating internal heat, thereby forming crystal nuclei and promoting crystal growth in a very short time, effectively avoiding the problems of long reaction time and uneven particle size distribution in traditional solvothermal methods. This invention is also synthesized under electron beam irradiation (electron beam current 1~10 mA, total irradiation dose 80~8000 kGy), which excites the organic solvent and reactants to generate free radicals, promoting rapid nucleation and crystallization through coordination self-assembly. This invention enables the rapid acquisition of highly crystalline and high-purity nano-MOF materials through microwave-assisted synthesis and electron beam irradiation synthesis, overcoming the bottlenecks of traditional solvothermal methods, such as uncontrollable particle size, long processing time, complex processes, and difficulty in scaling up.
[0017] The nano-MOFs material prepared in this invention has an extremely small grain size. This structural feature exposes a large number of adsorption active sites on the surface and significantly shortens the diffusion path of gas molecules, thereby significantly improving adsorption kinetics and demonstrating excellent adsorption and separation performance for xenon / krypton. This nano-MOFs material exhibits excellent dynamic adsorption and capture capabilities and separation selectivity for trace Xe / Kr mixtures, possessing excellent structural stability, good regeneration and recycling performance, and outstanding dynamic separation efficiency. It is particularly suitable for the dynamic separation of high-flow-rate, low-concentration Xe / Kr mixtures, offering advantages such as high selectivity, fast adsorption kinetics, and easy material regeneration. It has significant and promising application prospects in the fields of radioactive inert gas treatment and rare gas resource recovery.
[0018] As shown in the test results of the examples, when the Xe / Kr volume ratio is 20:80, the separation selectivity of the nano MOFs material for Xe / Kr at 1 bar is 29.55. Under the conditions of high flow rate of simulated nuclear waste feed gas (Xe 400ppm, Kr 40ppm, and the rest of the carrier gas) at 20 mL / min, the Xe / Kr permeation time ratio is as high as 32.6 times, the xenon capture amount is as high as 94.24 mmol / kg, and the adsorption performance remains stable after 5 adsorption-regeneration cycles, showing excellent adsorption stability. Attached Figure Description
[0019] Figure 1 X-ray powder diffraction patterns of nano-MOFs materials prepared under different electron beam irradiation conditions in Examples 1-9; Figure 2 X-ray powder diffraction patterns of nano-MOFs materials prepared under different microwave conditions in Examples 10-13; Figure 3 SEM image of the nano-MOFs material in Example 14; Figure 4 SEM image (partial magnification) of the nano-MOFs material in Example 14; Figure 5 X-ray powder diffraction pattern of the nano-MOFs material prepared in Comparative Example 1; Figure 6 The adsorption isotherms of xenon and krypton by the nano MOFs material in Application Example 1 are shown. Figure 7 The dynamic transmission curve of the nano-MOFs material in Application Example 2; Figure 8 The adsorption-regeneration cycle curves of the nano-MOFs material in Application Example 3 for five consecutive cycles; Figure 9 The dynamic transmission curve of the MOFs material prepared in Comparative Example 1 in Application Example 4; Figure 10 The dynamic transmission curve of the MOFs material prepared in Comparative Example 2 in Application Example 4; Figure 11 The dynamic transmission curve of the nano-MOFs material prepared in Example 10 of Application Example 4; Figure 12 The dynamic transmission curve of the nano-MOFs material prepared in Example 13 of Application Example 4; Figure 13 The dynamic transmission curve of the nano-MOFs material prepared in Example 14 of Application Example 4 is shown. Detailed Implementation
[0020] This invention provides a method for preparing nano-MOF materials, comprising the following steps: By mixing cyanuric acid, copper source, strontium source, alkali metal hydroxide and organic solvent, and carrying out microwave-assisted reaction or electron beam irradiation reaction, nano-MOF materials are obtained. The conditions for the microwave-assisted reaction include: power of 10~850 W, temperature of 60~150℃, and time of 0.5~120 min; The conditions for the electron beam irradiation reaction include: an electron beam current of 1~10 mA and a total irradiation dose of 80~8000 kGy; The particle size of the nano-MOFs material is 15~300 nm.
[0021] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.
[0022] This invention involves mixing cyanuric acid, a copper source, a strontium source, an alkali metal hydroxide, and an organic solvent, and then performing a microwave-assisted reaction or an electron beam irradiation reaction to obtain nano-MOF materials.
[0023] In this invention, the copper source may include copper chloride, copper bromide, or copper iodide. In this invention, the molar ratio of cyanuric acid to the copper source may be 1:(0.25~1), or 1:(0.4~0.8), or even 1:(0.5~0.6).
[0024] In this invention, the strontium copper source may include strontium chloride, strontium bromide, or strontium iodide. In this invention, the molar ratio of cyanuric acid to the strontium source may be 1:(0.25~1), or 1:(0.4~0.8), or even 1:(0.5~0.6).
[0025] In this invention, the alkali metal hydroxide may include sodium hydroxide and potassium hydroxide. The molar ratio of cyanuric acid to alkali metal hydroxide may be 1:(1~2.5), or 1:(1.5~2.2), or even 1:(1.8~2).
[0026] In this invention, the organic solvent may include methanol and / or ethanol, specifically methanol. In this invention, the ratio of cyanuric acid to organic solvent may be 1 mmol: 4~40 mL, or 1 mmol: 5~20 mL, or even 1 mmol: 10~15 mL.
[0027] In this invention, the mixing may include ultrasonic mixing. This invention does not have any special limitations on the conditions for ultrasonic mixing, as long as the raw materials are mixed evenly.
[0028] In this invention, the conditions for the microwave-assisted reaction include: a power of 10~850 W, which can be 50~600 W, specifically 10 W, 50 W, 100 W, 200 W, 300 W, 400 W, 500 W, 600 W, 700 W, 800 W or 850 W; a temperature of 60~150℃, which can be 80~140℃, specifically 80℃, 100℃, 120℃ or 140℃; and a time of 0.5~120 min, which can be 0.5~15 min, specifically 0.5 min, 1 min, 10 min, 15 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min.
[0029] In this invention, the conditions for the electron beam irradiation reaction include: an electron beam current of 1~10 mA, which can be 2~5 mA; and a total irradiation dose of 80~8000 kGy, which can be 100~6000 kGy, specifically 100 kGy, 200 kGy, 1000 kGy, 1500 kGy, 2000 kGy, 2400 kGy, 3000 kGy, or 6000 kGy.
[0030] This invention employs microwave-assisted synthesis or electron beam irradiation synthesis, enabling efficient, rapid, and controllable preparation of nano-MOF materials under mild conditions. It solves the problems of long time consumption, high energy consumption, and poor particle size uniformity of traditional solvothermal methods, and is easy to realize for continuous industrial production and large-scale scaling.
[0031] After completing the microwave-assisted reaction or electron beam irradiation reaction, the present invention further includes filtering the system after the microwave-assisted reaction or electron beam irradiation reaction, washing the obtained solid component, and drying it to obtain nano-MOF materials. In the present invention, the washing may include washing with methanol 2-4 times (specifically 3 times) or washing with water 2-4 times (specifically 3 times). In the present invention, the drying temperature may be 100-150℃, or 120-130℃, and the drying time may be 12-30 h, or 18-24 h. The present invention removes solvent molecules from the pores of the material through washing and drying.
[0032] The present invention also provides nano-MOFs materials prepared by the preparation method described in the above technical solution. In the present invention, the particle size of the nano-MOFs materials is 15~300 nm, and can also be 15~250 nm.
[0033] In this invention, the structural formation principle of the nano-MOFs material is as follows: the cyanuric acid ligand contains both nitrogen and oxygen coordination sites. Based on the hard-soft acid-base (HSAB) theory, the nitrogen atom preferentially binds to the soft acid metal ion Cu. 2+ Coordination, oxygen atoms preferentially interact with hard acid metal ions Sr 2+Coordination between the two leads results in a periodic, interwoven framework structure with regular octahedral cages. This bimetallic synergistic coordination strategy endows MOF materials with a highly ordered pore structure and abundant adsorption active sites. In terms of the synthesis mechanism, microwave-assisted synthesis enables rapid and uniform energy injection at the molecular level, causing instantaneous dipole rotation of the organic solvent and cyanuric acid ligand, generating internal heat. This leads to the formation of crystal nuclei and promotes crystal growth in a very short time, effectively avoiding the problems of long reaction times and uneven particle size distribution in traditional solvothermal methods. Electron beam irradiation synthesis utilizes a high-energy electron beam to directly excite solvent and reactant molecules, generating a large number of free radicals and active intermediates, inducing coordination reactions to be completed rapidly within seconds at room temperature and pressure, making it particularly suitable for large-scale preparation. Both methods employed in this invention overcome the limitations of traditional solvothermal methods, such as long reaction times, high energy consumption, and difficulty in controlling crystal size, achieving efficient, rapid, controllable, and large-scale preparation of nanoscale MOF materials. The nano-MOFs materials prepared by this invention have the advantages of excellent structural stability, excellent Xe / Kr dynamic adsorption and separation performance, and easy regeneration and recycling.
[0034] This invention also provides the application of the nano-MOFs material described in the above technical solution in the adsorption and separation of xenon and krypton.
[0035] The present invention also provides a method for separating xenon and krypton, comprising the following steps: The nano-MOFs material described in the above technical solution is vacuum activated to obtain activated MOFs material; The activated MOFs material is used to adsorb a mixture of xenon and krypton, thereby achieving the separation of xenon and krypton.
[0036] This invention involves vacuum activation of the nano-MOFs material described in the above-mentioned technical solution to obtain activated MOFs material. Specifically, the vacuum activation involves loading the nano-MOFs material into an adsorption column and performing vacuum activation. The vacuum activation temperature can be 20~140℃, or 80~120℃; the vacuum activation time can be 4~36 h, or 5~20 h, or even 8~12 h; and the vacuum degree can be 0~5.0 kPa, or 1~4.5 kPa, or even 2~4 kPa.
[0037] After obtaining the activated MOFs material, the present invention uses the activated MOFs material to adsorb a mixture of xenon and krypton, and then performs helium desorption to obtain xenon and krypton respectively.
[0038] In this invention, the xenon content in the mixed gas can be 200-600 ppm, or 300-500 ppm, specifically 400 ppm; the krypton content in the mixed gas can be 20-60 ppm, or 30-50 ppm, specifically 40 ppm; the remainder of the mixed gas is a carrier gas, which may include 78.96 vol% N2 and 21 vol% O2.
[0039] In this invention, the adsorption conditions may include: an adsorption temperature of 0~40℃, or 10~30℃, or 20~25℃; a total system pressure of 100~300 kPa, or 150~250 kPa, or specifically 200 kPa; and a mixed gas flow rate of 2~50 mL / min, or 10~40 mL / min, or 20~30 mL / min.
[0040] The present invention also provides a method for regenerating nano-MOFs materials after the separation method described above, comprising the following steps: desorbing the used nano-MOFs materials with helium to obtain regenerated nano-MOFs materials.
[0041] In this invention, the temperature for helium desorption can be 20~120℃, or 60~100℃, or specifically 80℃; the time for helium desorption can be 1~4 h, or 1.5~3 h, or even 2~3 h; the helium desorption can include helium purging desorption.
[0042] To further illustrate the present invention, the technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0043] In this invention, unless otherwise specified, the operating temperature is the ambient temperature.
[0044] Example 1 65 mg of cyanuric acid, 40 mg of sodium hydroxide, 40 mg of strontium chloride, and 34 mg of copper chloride were added to 5 mL of anhydrous methanol and sonicated to ensure thorough mixing, resulting in a suspension. The suspension was then placed in an electron beam irradiation apparatus for irradiation; the irradiation process did not require sealing. An irradiation dose of 100 kGy was applied at an electron beam current of 2 mA. After the reaction, the solid component was collected by filtration, washed three times with methanol and three times with ultrapure water, and dried in a vacuum oven at 120 °C for 24 h to obtain nano-MOF materials (deep blue).
[0045] Example 2 The only difference from Example 1 is that the irradiation dose is 200 kGy.
[0046] Example 3 The only difference from Example 1 is that the irradiation dose is 1000 kGy.
[0047] Example 4 The only difference from Example 1 is that the irradiation dose is 1500 kGy.
[0048] Example 5 The only difference from Example 1 is that the irradiation dose is 2000 kGy.
[0049] Example 6 The only difference from Example 1 is that the irradiation dose is 2400 kGy.
[0050] Example 7 The only difference from Example 1 is that the irradiation dose is 3000 kGy.
[0051] Example 8 The only difference from Example 1 is that the irradiation dose is 6000 kGy.
[0052] Example 9 The only difference from Example 1 is that the electron beam current is 5 mA and the irradiation dose is 6000 kGy.
[0053] X-ray powder diffraction patterns of nano-MOFs materials prepared under different electron beam irradiation conditions in Examples 1-9 are shown below. Figure 1 As shown, the PXRD patterns of each nano-MOF material are in high agreement with the standard simulated diffraction peaks, indicating that the nano-MOF materials were successfully synthesized.
[0054] Example 10 130 mg of cyanuric acid, 80 mg of sodium hydroxide, 80 mg of strontium chloride, and 68 mg of copper chloride were added to 10 mL of anhydrous methanol and sonicated to ensure thorough mixing, resulting in a suspension. The suspension was transferred to a sample tube, sealed, and placed in a microwave synthesizer. Microwave treatment was performed at 600 W. After the reaction, the mixture was cooled to room temperature, filtered, and the solid component was collected. The solid was washed three times with methanol and three times with ultrapure water, and then dried in a vacuum oven at 120 °C for 24 h to obtain nano-MOF materials (deep blue). The microwave treatment temperature and time were 140 °C for 60 seconds.
[0055] Example 11 The only difference from Example 10 is that the temperature and time conditions for microwave treatment are microwave heating at 140°C for 10 minutes.
[0056] Example 12 The only difference from Example 10 is that the temperature and time conditions for microwave treatment are microwave heating at 80°C for 15 minutes.
[0057] Example 13 The only difference from Example 10 is that the temperature and time conditions for microwave treatment are microwave heating at 80°C for 30 seconds.
[0058] The X-ray powder diffraction patterns of nano-MOFs materials prepared under different microwave conditions in Examples 10-13 are shown below. Figure 2 As shown, the PXRD patterns of each nano-MOF material are in high agreement with the standard simulated diffraction peaks, indicating that the nano-MOF materials were successfully synthesized.
[0059] Example 14 The only difference from Example 10 is that the temperature and time conditions for microwave treatment are microwave heating at 140°C for 2 hours.
[0060] SEM images of the microstructure of the nano-MOFs material prepared in Example 14 are shown below. Figure 3 and Figure 4 As shown, the obtained MOF material is an octahedral nanoparticle with a particle size of 15~250 nm.
[0061] Comparative Example 1 325 g of cyanuric acid, 200 g of sodium hydroxide, 200 g of strontium chloride, and 170 g of copper chloride were added to 1.8 L of anhydrous methanol and stirred until thoroughly mixed. The suspension was transferred to a flask and refluxed at 120 °C for 3 days. After the reaction was complete, the mixture was cooled to room temperature, filtered to collect the solid fraction, washed three times with methanol and three times with ultrapure water, and dried in a vacuum oven at 120 °C for 24 h to obtain MOFs material (deep blue). The X-ray powder diffraction pattern of this comparative example is shown below. Figure 5 As shown, compared with the microwave-synthesized sample, the diffraction peaks of this sample are wider and the peak intensities are lower, indicating that although the target phase has been successfully synthesized, its crystallinity is relatively low.
[0062] Comparative Example 2 Based on the synthesis method of the metal-organic framework material CuSr(HC3O3N3)2 in the reported patent CN121801108A, a non-nanoscale MOF material CuSr(HC3O3N3)2 was synthesized: 130 mg of cyanuric acid, 80 mg of sodium hydroxide, 80 mg of strontium chloride, and 68 mg of copper chloride were added to 10 mL of anhydrous methanol and sonicated to ensure thorough mixing, resulting in a suspension. The suspension was transferred to a reaction vessel, sealed, and subjected to a high-temperature and high-pressure reaction at 120 °C for 72 h. After the reaction, the mixture was cooled to room temperature, filtered to collect the solid component, washed three times with methanol and three times with ultrapure water, and dried in a vacuum oven at 120 °C for 24 h to obtain the MOF material (dark blue).
[0063] Application Example 1 The nano-MOFs material obtained in Example 14 was subjected to static adsorption tests. Single-component adsorption isotherms of the nano-MOFs material for xenon and krypton were measured at 0°C (273 K) and 25°C (298 K), as shown below. Figure 6 As shown in the figure. Tests showed that at 25℃ and 1 bar, the adsorption capacity of this nano-MOF material for xenon was 1.92 mmol / g, and for krypton it was 1.33 mmol / g. Based on the adsorption isotherm data, calculations using IAST (Ideal Adsorption Solution Theory) showed that when the xenon / krypton volume ratio was 20:80, the separation selectivity of this nano-MOF material for xenon / krypton at 1 bar was 29.55, which is higher than most reported high-performance materials, such as CC3 with IAST = 12.5.
[0064] Application Example 2 To test the dynamic adsorption performance of the nano-MOFs material, a dynamic breakthrough test was performed on the nano-MOFs material obtained in Example 14. The nano-MOFs material was packed into an adsorption column and activated at 120°C under vacuum (4.0 kPa) for 8 h. A mixed gas (400 ppm xenon, 40 ppm krypton, with the remainder as carrier gas, consisting of 78.96 vol% N2 and 21 vol% O2) was introduced into the adsorption column. A fixed-bed breakthrough test was conducted at an adsorption temperature of 25°C, a total system pressure of 100 kPa, and a mixed gas flow rate of 20 mL / min. The dynamic breakthrough curve is shown below. Figure 7 As shown in the figure, experimental data indicate that krypton begins to penetrate at 6.3 min / g, while xenon begins to penetrate at 205.6 min / g, with a Xe / Kr penetration time ratio of 32.6 times. This demonstrates that the nano-MOF material can achieve efficient separation of xenon-krypton mixtures. Furthermore, the dynamic adsorption capacity of the nano-MOF material for xenon is 94.24 mmol / kg, indicating its excellent xenon capture capability.
[0065] Compared with the previously reported non-nanoscale material (CN121801108A, the adsorbent capture amount of Xe is 92.6 mmol / kg at a flow rate of 5 mL / min), the nano-MOF material prepared in this invention can still achieve a capture amount of 94.24 mmol / kg of Xe at a higher flow rate (20 mL / min), demonstrating excellent xenon capture performance at high flow rates.
[0066] Application Example 3 To test the cyclic adsorption performance of the nano-MOFs material, an adsorption-regeneration cycle experiment was conducted on the nano-MOFs material obtained in Example 14. The nano-MOFs material was packed into an adsorption column and activated under vacuum at 120°C for 8 h. A mixed gas (400 ppm xenon, 40 ppm krypton, with the remainder as carrier gas, consisting of 78.96 vol% N2 and 21 vol% O2) was introduced into the adsorption column, and a dynamic breakthrough test was performed at an adsorption temperature of 25°C, a total system pressure of 100 kPa, and a mixed gas flow rate of 10 mL / min. Breakthrough was stopped once xenon penetration was complete, and helium was used for purging and desorption at 80°C for 2 h. The results are as follows: Figure 8 As shown, the adsorption performance remains stable even after five consecutive adsorption-regeneration cycles of the adsorption column, indicating that the nano MOFs material has excellent cyclic adsorption performance stability.
[0067] Application Example 4 The dynamic adsorption properties of MOFs materials prepared in Examples 10, 13, 14, and Comparative Example 1, as well as the MOFs material prepared in Comparative Example 2, are compared. The only difference from Application Example 2 is that the total flow rate of the mixed gas is 5 mL / min.
[0068] The dynamic adsorption results of the MOFs material prepared in Comparative Example 1 are shown in the figure. Figure 9 The Kr breakthrough time was 11.55 min / g, the Xe breakthrough time was 158.14 min / g, and the dynamic adsorption capacity of Xe was 56.07 mmol / kg. The dynamic xenon-krypton separation performance and xenon adsorption capacity were significantly reduced, possibly due to insufficient reflux synthesis in large batches, resulting in low crystallinity of the material and thus deteriorating performance.
[0069] The dynamic adsorption results of the MOFs materials prepared in Comparative Example 2 are shown in the figure. Figure 10The Kr breakthrough time was 16.95 min / g, the Xe breakthrough time was 571.67 min / g, and the dynamic adsorption capacity of Xe was 77.05 mmol / kg. Compared with the previously reported data (CN121801108A, the adsorbent capture of Xe at a flow rate of 5 mL / min was 92.6 mmol / kg, and the Xe breakthrough time was 392 min), the dynamic adsorption capacity of Xe was lower, while the breakthrough time was longer.
[0070] The dynamic adsorption results of the nano-MOFs material prepared in Example 10 are shown in the figure. Figure 11 The Kr breakthrough time was 12.55 min / g, the Xe breakthrough time was 469.33 min / g, and the Xe dynamic adsorption capacity was 58.21 mmol / kg. Compared with Example 14, the reaction temperature of Example 10 was lower and the reaction time was shorter, which may have resulted in insufficient reaction. Therefore, the dynamic xenon-krypton separation effect showed a certain decrease compared with Example 14.
[0071] The dynamic adsorption results of the nano-MOFs material prepared in Example 13 are shown in the figure. Figure 12 The Kr breakthrough time was 12.42 min / g, the Xe breakthrough time was 458.465 min / g, and the Xe dynamic adsorption capacity was 57.86 mmol / kg. Compared with Example 14, the reaction temperature of Example 13 was lower and the reaction time was shorter, which may have resulted in insufficient reaction. Therefore, the dynamic xenon-krypton separation effect showed a certain decrease compared with Example 14.
[0072] The dynamic adsorption results of the nano-MOFs material prepared in Example 14 are shown in the figure. Figure 13 Experimental data showed that krypton began to penetrate at 5.18 min / g, while xenon only began to penetrate at 641.19 min / g, indicating that the nano-MOFs material can achieve efficient separation of xenon-krypton mixtures. Furthermore, the dynamic adsorption capacity of the nano-MOFs material for xenon was 81.38 mmol / kg, demonstrating its excellent xenon capture ability. Compared with the dynamic adsorption results of the non-nano-MOFs material prepared in Comparative Example 2, xenon exhibited a longer penetration time and a higher adsorption capacity. This indicates that, under the same test conditions, although the material prepared by the solvothermal method still possesses good Xe / Kr separation performance, its Xe retention capacity and dynamic adsorption capacity are lower than those of Example 14.
[0073] The above results indicate that microwave-synthesized nano-MOFs exhibit longer Xe breakthrough time and higher dynamic Xe adsorption capacity, with overall xenon-krypton separation performance superior to materials synthesized by solvothermal methods. It is speculated that nano-sizing may shorten the diffusion path of gas molecules within the particles, improve mass transfer kinetics, and allow for more efficient utilization of adsorption active sites.
[0074] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing nano-MOF materials, characterized in that, Includes the following steps: By mixing cyanuric acid, copper source, strontium source, alkali metal hydroxide and organic solvent, and carrying out microwave-assisted reaction or electron beam irradiation reaction, nano-MOF materials are obtained. The conditions for the microwave-assisted reaction include: power of 10~850 W, temperature of 60~150℃, and time of 0.5~120 min; The conditions for the electron beam irradiation reaction include: an electron beam current of 1~10 mA and a total irradiation dose of 80~8000 kGy; The particle size of the nano-MOFs material is 15~300 nm.
2. The preparation method according to claim 1, characterized in that, The molar ratio of cyanuric acid to copper source is 1:(0.25~1). The molar ratio of cyanuric acid to strontium source is 1:(0.25~1); The molar ratio of cyanuric acid to alkali metal hydroxide is 1:(1~2.5).
3. The preparation method according to claim 1, characterized in that, The organic solvents include methanol and / or ethanol.
4. The nano-MOF material prepared by the preparation method according to any one of claims 1 to 3.
5. The application of the nano-MOFs material according to claim 4 in the adsorption and separation of xenon and krypton.
6. A method for separating xenon and krypton, characterized in that, Includes the following steps: The nano-MOFs material described in claim 4 is vacuum activated to obtain activated MOFs material; The activated MOFs material is used to adsorb a mixture of xenon and krypton, thereby achieving the separation of xenon and krypton.
7. The separation method according to claim 6, characterized in that, The vacuum activation temperature is 20~140℃, and the time is 4~36 h.
8. The separation method according to claim 6, characterized in that, The mixture contains 200-600 ppm xenon and 20-60 ppm krypton.
9. The separation method according to claim 6 or 8, characterized in that, The adsorption conditions include: an adsorption temperature of 0~40℃, a total system pressure of 100~300 kPa, and a mixed gas flow rate of 2~50 mL / min.
10. A method for regenerating nano-MOFs materials after use of the separation method according to any one of claims 6 to 9, characterized in that, The process includes the following steps: desorbing the used nano-MOFs material with helium to obtain regenerated nano-MOFs material.
Citation Information
Patent Citations
Metal organic framework material for adsorbing and separating xenon and krypton as well as preparation method and application of metal organic framework material
CN121801108A